The clinical expression of bullous pemphigoid is not determined by the specificity of the target antigen. - Venning, V; Whitehead, P; Leigh, I; Allen, J; Wojnarowska, F (1991)
The major bullous pemphigoid (BP) antigen is a 220-240-kDa polypeptide, although some BP sera recognize bands of 180-200 kDa or lower molecular weight. We have investigated to what extent this heterogeneity of the target antigen accounts for the clinical diversity of BP. Immunoblotting studies against extracts of salt-separated epidermis were performed on sera from 39 patients with BP. The blotting patters obtained were correlated with the clinical findings, with particular reference to prodromal itching, lesion morphology and severity, mucosal involvement, presence of milia, dapsone responsiveness and disease duration. The results confirm that the major BP antigen is a 220-kDa polypeptide, and that the 180-kDa polypeptide is a second and sometimes the sole BP antigen identified in immunoblots. Rarely, multiple bands of lower molecular weight were found. There was no correlation between the pattern of BP antigens detected in immunoblots and the clinical presentation and course of BP. There was considerable clinical diversity even among the nine patients showing specificity for a single 220-kDa target antigen. Although two patients with a single 180-kDa antigen specificity had a disease of unusually long duration, factors other than antigen specificity must determine the clinical expression of BP.